Improving ultra wideband (UWB) system by modified random combination of pulses - Goyal, Vikas (Array, 2018)
Ultra-Wideband (UWB) technology uses very narrow pulses of nano-seconds duration to provide very high data rates. The pulses to be used for the UWB are very important and should meet the emission mask regulatory requirements to get good performance when transmitted over the channel. To meet these requirements, a combination of higher order derivatives of Gaussian pulses can be considered to form a combined pulse instead of transmitting them separately. The main aim of this paper is to improve the performance of Ultra Wideband (UWB) multiple access modulation system with a newly Proposed combined pulse, generated using a modified random pulse combining of the first five Gaussian derivative pulses with optimal shaping factors as basic functions. In order to meet the UWB power spectrum regulations, the power spectral utilization of the newly designed pulse is calculated and the bit error rate performance of the pulse position modulation time hopping system using the newly proposed pulse is analyzed in a multi-path channel environment using RAKE receiver. The simulation results carried out in MATLAB software shows that the new proposed combined pulse has higher pulse energy matching the spectral limits of UWB and an improved bit error rate performance as compared to the previous literature results.